Pengaruh Media Sosial Terhadap Pemahaman Generasi Muda Mengenai HAM - Anggun Dwi Andriani; Murny Murny; Renaningtyas Putri Lestari; Utami Widia Putri (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
analyze the impact of social media on young people’s knowledge of Human Rights (HAM). Social media, as the primary channel for communication and information for young people, has a significant ability to shape their views and understanding of human rights. This study will examine how social media content, both supportive and anti-human, influences young people’s understanding, attitudes, and actions about human rights. In addition, this study will also investigate the function of social media in raising human rights awareness, and identify challenges and opportunities in utilizing social media for human rights education and advocacy among young people. The results of this study are expected to contribute to the development of effective strategies in using social media to increase understanding and awareness of human rights among young people.